1988
DOI: 10.1007/bf00449911
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neurobiological findings in children suffering from tic disease following treatment with tiapride

Abstract: Tiapride, a substituted benzamide derivative, possesses good clinical antidyskinetic properties due to its DA2-blocking activities. It has been shown to be clinically effective in the treatment of tic disease in children. In order to study tiapride's antidyskinetic properties in the treatment of the tic syndrome in children, we conducted a simple, placebo-controlled study on 10 children followed by a double-blind crossover study on 17 children. Tiapride was shown to have a positive therapeutic effect on tics i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
1
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 8 publications
1
46
1
4
Order By: Relevance
“…First, the inclusion of clinically referred children with CTD and=or ADHD limits the generalizability of our findings to epidemiological samples. Second, continuation of antipsychotics in some children during testing might have confounded the results, although e.g., for both tiparide (Rothenberger and Eggers 1982;Eggers et al 1988) and risperidone (Allain et al 2003) there is no evidence of influencing cognitive performance in short-term low-dose medication in healthy volunteers or children with tic disorders. Third, the use of a single clinical measure of color perception (FMT), requiring substantial capacities in sustained attention, should be seen with caution in testing children with ADHD free of stimulant medication.…”
Section: Discussionmentioning
confidence: 99%
“…First, the inclusion of clinically referred children with CTD and=or ADHD limits the generalizability of our findings to epidemiological samples. Second, continuation of antipsychotics in some children during testing might have confounded the results, although e.g., for both tiparide (Rothenberger and Eggers 1982;Eggers et al 1988) and risperidone (Allain et al 2003) there is no evidence of influencing cognitive performance in short-term low-dose medication in healthy volunteers or children with tic disorders. Third, the use of a single clinical measure of color perception (FMT), requiring substantial capacities in sustained attention, should be seen with caution in testing children with ADHD free of stimulant medication.…”
Section: Discussionmentioning
confidence: 99%
“…In a placebo-controlled, double-blind, crossover trial, Eggers and colleagues found that tiapride improved tics in children and had no adverse effect on cognitive function [Eggers et al 1988].…”
Section: Other Pharmacological Agentsmentioning
confidence: 99%
“…69 The specific D2 receptor-blocking agents, tiapride and sulpiride, are commonly used for the treatment of tics in Europe, but they are not available in the United States. 70,71 In doses ranging from 5 to 6 mg/kg body wt/day, tiapride was superior to placebo in decreasing tics after 6 weeks of treatment in 27 children with TS. 70 A retrospective study of sulpiride in 63 patients with TS (age 10 to 68 years) reported a positive response in more than 50% of the sample.…”
mentioning
confidence: 97%
“…70,71 In doses ranging from 5 to 6 mg/kg body wt/day, tiapride was superior to placebo in decreasing tics after 6 weeks of treatment in 27 children with TS. 70 A retrospective study of sulpiride in 63 patients with TS (age 10 to 68 years) reported a positive response in more than 50% of the sample. 71 Because several patients were also receiving other medications for tics, it is difficult to assess the benefits of sulpiride on tics.…”
mentioning
confidence: 97%